An ecological history of modern China - Harrell, Stevan 1947- (University of Washington Press, 2023)
"Is environmental degradation an inevitable result of economic development? Can ecosystems be restored once government officials and the public are committed to doing so? These questions are at the heart of An Ecological History of Modern China, a comprehensive account of China's transformation since the founding of the People's Republic from the perspective not of the economy but of the biophysical world. Examples throughout illustrate how agricultural, industrial, and urban development have affected the resilience of China's ecosystems-their ability to withstand disturbances and additional growth-and what this means for the country's future. Drawing on decades of research, Stevan Harrell demonstrates the local and global impacts of China's miraculous rise. In clear and accessible prose, An Ecological History of Modern China untangles the paradoxes of development and questions the possibility of a future that is both prosperous and sustainable. It is a critical resource for students, scholars, and general readers interested in environmental change, Chinese history, and sustainable development."
Includes bibliographical references and index
Keywords: Geschichte 1949-; Ökosystem; Umwelt; China; Environmental sciences / China; Economic development / Environmental aspects / China; Ecology / China; Environmental policy / China